Acute Pancreatitis Causing Descending Colonic Stricture: A Rare Sequelae. (March 2019) - Mandal, Amrendra Kumar; Kafle, Paritosh; Puri, Pradip; Chaulagai, Baikuntha; Hassan, Muhammad; Bhattarai, Bikash; Kanth, Rajan; Gayam, Vijay
An isolated descending colonic stricture is an unlikely complication of acute pancreatitis, with the nonspecific symptoms of colonic stricture making the overall diagnosis difficult. Crohn's disease (CD) and tuberculosis (TB) are the two common etiologies of an isolated colonic stricture and may present similarly to colonic stricture related to acute pancreatitis. Unfortunately, colonoscopy and biopsy often cannot determine the etiology, and surgical resection may be needed to provide both symptomatic relief and confirm the diagnosis. As a result, descending colonic stricture may produce a diagnostic dilemma with CD and TB as all 3 conditions may be radiologically and endoscopically indistinguishable. We describe a young male with weight loss and abdominal pain. TB testing was negative, with radiography and ELISA (enzyme-linked immunosorbent assay) testing supporting a diagnosis of the CD. The patient was initiated on sulfasalazine but worsened over the next month. Further investigations revealed that the patient had descending colonic stricture without CD. Therefore, the stricture's etiology was most likely related to an episode of acute pancreatitis the patient had 2 months before admission and was found to have left colonic segment adherent to the pancreas eventually requiring segmentectomy. Although the pathophysiology of colonic stricture after pancreatitis is unclear, we speculate that inflammatory injury to the colon is an important component. Finally, we emphasize that colonic stricture is a rare complication of pancreatitis.